(untitled) (Bangladesh Journal of Pharmacology, 2014)
The increase in antibiotic resistance has resulted in decreasing number active antimicrobial agents available to treat infections by multidrug resistant (MDR) bacteria. The aim of this study was to determine the antimicrobial activity of the extracts of Glaucium elegans and saffron (Crocus sativus) onios plant species against Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, Bacillus anthracis and Proteus by disc diffusion method. The methanol extract of G. elegans was found to have a significant antibacterial efficiency (p<0.05) as compared to the methanol extract of onios plant. These finding pinpoint the efficiency of these extracts to inhibit microbial growth. The bactericidal activity described here represents an added safety value for G. elegans possesses the significant antibacterial activity.